A estética nas narrativas (auto) biográficas no espaço escolar: contribuições à gestão na sala de aula - Duarte, Francisco Maia (2021)
This work aims to understand the aesthetic dimension of students' narratives in the school space in the constitution of autonomy and emancipation in learning environments. The concepts of subjects' autonomy and emancipation as aesthetic values will be explored in the perspective of Adorno (2002; 1995), Paulo Freire (1967; 1995; 1996; 1997; 2000) and Schiller (2014). It is adopted to understand the spaces Bourdieu (2002), Frago and Escolano (1998), Foucault (2006) and Kowaltowski (2011). The data collection used will be “Colcha de Retalhos”, in Berkenbrock-Rosito (2008; 2009; 2014) which aims at the production of autobiographical narratives in three dimensions: written, oral and pictorial of High School students integrated to the technician in Business Administration. a high school and technical school on the east side of São Paulo. The approach is qualitative and thematic analysis is used to or ganize the data, from the perspective of Jovchelovitch and Bauer (2002), analysis of the data under the hermeneutic approach, from the perspective of Gadamer (2000). This study presents a contribution to the understanding of school management as a possibility of reflecting the aesthetic dimension in school spaces through the students' narratives and shows the importance of the “Quilt of Patchwork” as a listening methodology. The (auto) biographical narratives constituted a movement of reconstruction and allowed space for listening to oneself and the other, which can be used as an intervention in the management of the classroom and outside it in the learning spaces, in order to expand the possibilities in the constitution the subjects' autonomy and emancipation.